Pengaruh Budaya Etis Organisasi, Keadilan Organisasi dan Moralitas Aparatur Terhadap Kecurangan Akuntansi dengan Penguatan Kualitas Pengendalian Internal SKPD di Kota Bengkalis - Fiani, Sofiani; Fiddin, Fachroh (P3M Politeknik Negeri Bengkalis, 2024)
This study aims to determine the influence of organizational ethical culture, organizational justice, and the quality of internal control in minimizing accounting fraud, with the reinforcement of the morality of local government unit apparatus in Bengkalis city. This research is a quantitative study with a descriptive approach. The sampling method used was purposive sampling, with a sample size of 88 respondents. The data used in the study is primary data collected through direct questionnaire surveys. The data analysis employs multiple linear regression analysis and moderating regression analysis using the residual test approach. Multiple linear regression analysis was applied for the hypothesis of organizational ethical culture, while multiple linear regression analysis with a residual test was used for organizational justice moderated by the quality of internal control.